Konsep Dasar Evaluasi Pembelajaran di Sekolah Dasar Negeri Gintung I Kecamatan Sukadiri - Magdalena, Ina; Ramadanti, Saskia; Ramdhan, Savina Nurrahmadanti; Luftiyah, Vivi (Lembaga Yasin AlSys, 2023)
Based on observations that have been made with interview with teachers conducted at SD Negeri Gintung I, Which relates to the basic concept of evaluation. Based on the results of interview conducted by researchers to teacher evaluation consists of measurement and assesment. In the context of learning evaluation has a very important and strategic position, because it is included in the steps of learning. The aim is to find out the effectiveness and efficiency of the learning system. The environment includes evaluating learning programs, learning processes and learning outcomes. In general, the evaluation princple consists of continuity, comperehnsive, fair, objective, cooperative and practical. Specifically, the princple consists of cohesiveness, coherence, padagogy, and accountability. In terms of type evaluation of learning consists of evaluating planning, devolopment, monitoring, impact, efficiency, and comperehensive programs.